Beyond productivity: The socio-cultural role of fishing among the Baka of southeastern Cameroon - Sandrine Gallois; Romain Duda (Revue d'ethnoécologie)
For long, the importance of fishing for forest societies has been hiding behind the term “hunter-gatherers”. Whereas the importance of hunting is commonly recognized among such societies, some research has also highlighted that fishing is a primordial resource for subsistence, as well as a key element in the cosmology of several forest societies. However, very few studies — and less so among Central African forest societies — have focused on fishing practices and their social, cultural and symbolic complexity. To contribute to fill this gap, we analyze fishing activities among two Baka communities from southeastern Cameroon, particularly focusing on fishing productivity as well as the ethnoecological specificities and the socio-cultural role of fishing. Data were collected through interviews and systematic observations of fishing activities carried out with children and adults and weekly interviews on productivity carried out during twelve months (n = 272 individuals). Results of this study highlight that fishing, and most specifically dam fishing, a collective women fishing technique, bears a specific place in Baka society. In contrast with hunting, whose value is mostly associated to the cultural valorization of the wild meat, the cultural importance of fishing is largely based on the activity in itself, through its socio-cultural dimension. Dam fishing creates a specific space where, in the absence of men, women create social cohesion through exchanges and sharing. Furthermore, dam fishing represents a privileged space for learning, because it allows not only the transmission of ethnoichthyological knowledge, but also the transmission of other aspects of cultural knowledge that shape the early gender differentiation between boys and girls. This paper aims to highlight the socio-cultural value of fishing activities in the livelihood of contemporary forest hunter-gatherers.